Melik Nasır II. Salahaddin Yusuf devrinde Eyyubiler Devleti (Hicri 634-659/ Miladi 1236-1261) - Kılıç, Mustafa (My University, 2001)
unknown
Keywords: 500-1199; Dünya tarihi; Eyyubi Devleti-Tarih; Ortaçağ_Tarih; Tarih